Perkembangan Kesenian Marawis di Madrasah Al-Istiqomah Tahun 2015 -2019 - Dina Oktaviani; Aam Abdillah (Priangan: Journal of Islamic Sundanese Culture, 2023)
AbstractArt is something that comes out of human hands, both in the form of sound and work. In this study the author will discuss the history of Marawis art at Madrasa Al-Istiqomah, with the development of the Marawis era at Madrasahs developing according to the demands of the times. Marawis in Madrasas is one that still maintains Marawis art, competing with the times which have not lost the characteristics of the Marawis art itself. The method used in this study is the historical historical method which consists of heuristics, criticism, interpretation and historiography. The results of the study show that the Marawis art was originally used for Islamic celebrations and major events, now Marawis is also used in weddings, circumcisions, birthday celebrations for madrasahs, Islamic boarding schools or institutions, even in competitions in arts festivals. Keywords: Development, Art, Marawis, Madrasah Al-Istiqomah  AbstrakKesenian merupakan suatu hal yang keluar dari tangan manusia baik berupa suara maupun hasil karya. Dalam penelitian ini penulis akan membahas terkait sejarah kesenian Marawis di Madrasah Al-Istiqomah, dengan perkembangan zaman Marawis di Madrasah berkembang sesuai dengan tuntutan zaman. Marawis di Madrasah merupakan salah satu yang masih mempertahankan kesenian Marawis, bersaing dengan perkembangan zaman yang mana tidak memghilangkan ciri khas dari kesenian Marawis itu sendiri. Metode yang digunakan dalam penelitian ini adalah metode history sejarah yang terdiri dari heuristik, kritik, interpetasidan historiografi. Hasil penelitian menunjukan bahwa kesenian Marawis yang awalnya dipergunakan untuk syiar dan acara besar Islam, sekarang ini Marawis juga dipergunakan dalam acara nikahan, khitanan, perayaan ulang tahun madrasah, pesantren atau institusi-institusi bahkan di perlombaan dalam festival-festival kesenian. Kata kunci: Perkembangan, Kesenian, Marawis, Madrasah Al-Istiqomah